2000
DOI: 10.1159/000053622
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sialyl Glycoconjugates in Eosinophil-Specific Granules after Degranulation Stimuli

Abstract: Sialyl glycoconjugates, a group of the acidic glycoconjugates, are expressed in murine eosinophil-specific granules through their maturational stages. To clarify whether the sialyl glycoconjugates work as functional molecules in the process of eosinophil degranulation, we examined the localization of sialyl residues after degranulation stimulated with calcium ionophore A23187 or interleukin-5. Although sialyl residues were localized in the specific granules before degranulation, they were dissociated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies have observed that carbohydrates of eosinofils surface are involved in the degranulation process (Ohmori & Nawa, 2000), fact which raised attention for the importance of expression and liberation of products from cells in the hepatic granulomas acting as fibrosis inhibitors (van de Vijver et al, 2006). Lectin binding intensity can be influenced by the stage of development of the Schistosoma egg, reflecting the content of carbohydrates in the egg tegument.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have observed that carbohydrates of eosinofils surface are involved in the degranulation process (Ohmori & Nawa, 2000), fact which raised attention for the importance of expression and liberation of products from cells in the hepatic granulomas acting as fibrosis inhibitors (van de Vijver et al, 2006). Lectin binding intensity can be influenced by the stage of development of the Schistosoma egg, reflecting the content of carbohydrates in the egg tegument.…”
Section: Resultsmentioning
confidence: 99%